LEARNING LIFE BALANCE: A STUDY TO REGAIN MENTAL PEACE AND MENTAL HEALTH OF SENIOR HIGH STUDENTS - R. Madhakomala; Johansyah Anwar (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2017)
The aim of this study is to observe the level of happiness enmjoyed among senio high students related to current school practices and national learning system regulated by the authorities.The world of learning has changed when school grading has been becoming as one of the most obligating and influencing source of educational success in within the institution. The historical myth of study with fun and enjoyment has gradually but sure moved to the sense of study hard for the sake of the future by consuming most of the daytime hours.Nevertheless, this is when the problem of lack of students’ quality time commences. Students do not realize that they are moving to the unsatisfied part of the learning life, as so many times they are also intrigued with and by computers; when unconsiously they lose the lovely ones and the world outside.This study attempts to show how senior high students can achieve the so-called learning life balance to regain their mental peace by more contacts and relationships with families, the environment, and the world around. This is how the world of educating has to recognize and understand the value of happiness of a senior high student. This is how the regulator has to manage the system to flow to the building and the establishment of the well-being of nowadays students.